Ethics of Artificial Intelligence in MaqÄá¹£id Al-SharÄ«a's Perspective - Habib, Zainal (KARSA Journal of Social and Islamic Culture, 2025)
The rapid development of Artificial Intelligence (AI) has brought significant transformation across various sectors but also presents complex and urgent ethical challenges. Key issues include algorithmic bias that may reinforce social discrimination, privacy violations due to massive data collection without adequate control, and unclear accountability in autonomous AI systems. These challenges threaten social justice, individual rights, and public trust in technology. This study aims to develop an AI ethics framework grounded in MaqÄá¹£id al-SharÄ«Ê¿a, the Islamic legal philosophy emphasizing the protection of five fundamental values: religion (á¸¥ifáº“ al-dÄ«n), life (á¸¥ifáº“ al-nafs), intellect (á¸¥ifáº“ al-Ê¿aql), lineage (á¸¥ifáº“ al-nasl), and property (á¸¥ifáº“ al-mÄl). A qualitative literature review method employing content analysis and thematic synthesis was applied to examine relevant literature on AI ethics and MaqÄá¹£id al-SharÄ«Ê¿a, identifying gaps and opportunities for normative integration. The findings demonstrate that MaqÄá¹£id al-SharÄ«Ê¿a offers a holistic perspective complementing Western AI ethics frameworks by incorporating spiritual, moral, and social justice dimensions. The principle of á¸¥ifáº“ al-Ê¿aql underpins efforts to combat misinformation, while á¸¥ifáº“ al-mÄl guides the equitable development of Sharia-compliant fintech. This study recommends inclusive algorithm design, Sharia-based regulation, and multidisciplinary collaboration among religious scholars, technology developers, and regulators to ensure ethical, responsible, and sustainable AI development.